Commanding and Requesting: Teachers’ Speech Acts in Indonesian Vocational English Schools - Arbain Arbain; Gunawan, Fahmi; Al Haddar , Gamar; Sitinjak , Charli (Forum for Linguistic Studies, 2024)
Effective communication in the classroom profoundly influences educational performance, particularly in language acquisition settings. This study investigates the employment of directive (commanding) and requestive (requesting) speech acts by English educators in Indonesian vocational high schools, a subject that remains under-examined. This research utilizes a qualitative case study design to examine the utilization of speech actions by teachers and their perceptions by students. Data were gathered by classroom observations, audio recordings, and semi-structured interviews with five English educators and five students from a vocational institution in Samarinda, Indonesia. The results indicate that directed speech acts are predominantly employed to uphold discipline and deliver explicit instructions, hence enhancing classroom management and concentration. In contrast, requestive speech acts foster a polite environment that promotes active student engagement and collaboration. Furthermore, educators deliberately integrate the Indonesian language to augment students' understanding and involvement. The study highlights the necessity of a judicious application of both commanding and requesting speech acts to facilitate effective teaching practices that integrate authority with mutual respect. These discoveries have considerable significance for teacher training programs, indicating that professional development should prioritize the incorporation of communication tactics that adjust to classroom dynamics and promote a good learning atmosphere. Utilizing multilingual methodologies and contextually relevant communication can enhance teacher-student interactions, hence improving student engagement and educational results.